CULTURAL BASED TOURISM DEVELOPMENT IN PASIR PUTIH VILLAGE TUKAK SADAI DISTRICT, BANGKA SELATAN DISTRICT THROUGH AGIK BARIK FESTIVAL - Darwance Darwance; Dwi Haryadi; Izma Fahria; Agung Samudra; Desy Ramadhanty; Erika Erika (Faculty of Social and Political Sciences University of Bangka Belitung, 2019)
Education, culture and tourism are three things that cannot be separated and interconnected. Culture will develop if education develops too. By education, culture will increase the development of tourism in Indonesia. In order to improve the quality and progress of education, culture and tourism, Social Service Lecture (KKN) XIV Bangka Belitung University (UBB) 2019 Pasirputih - Sadai Desa Pasirputih region, develop tourist destinations through the program